A description of U.S. enlisted personnel promotion systems - Williamson, Stephanie, 1969- (RAND, 1999)
The U.S. armed services have different methods and processes for promoting enlisted personnel. All of the services, however, aim to ensure that promotion outcomes correspond to substantive differences in personnel quality. This report provides a snapshot of how the Army, Navy, Marines, and Air Force go about measuring duty performance, leadership potential, experience, knowledge, and skills to determine who among its enlisted force merits promotion, when they are eligible for promotion, and at what level promotion decisions are made. This report provides an overview of the enlisted promotion system in the 1990s as retention issues again move to the forefront of Defense Department concerns.